1993
DOI: 10.1139/x93-034
|View full text |Cite
|
Sign up to set email alerts
|

A time to ignition–temperature–moisture relationship for branches of three western conifers

Abstract: The effect of convection column air temperature and live needle moisture content on ignitability of tree branches was verified and quantified by exposing branches of three conifer species to a hot-air convection column, at temperatures between 400 and 640 °C, and measuring time to ignition. The three species were ponderosa pine (Pinusponderosa Laws.), Douglas-fir (Pseudotsugamenziesii var glauca (Beissn.) Franco), and lodgepole pine (Pinuscontorta Dougl.). The experiment was repeated monthly over the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 0 publications
2
37
0
1
Order By: Relevance
“…Table 1 summarizes basic descriptive statistics of the independent variables selected for analysis. Foliar moisture content, canopy base height, and wind speed are three fire environment variables that theoretically are major factors controlling the onset of crowning and have already been used in modeling this phenomenon (Van Wagner 1977a, Xanthopoulos 1990, Alexander 1998Cruz et al 2002). The range and deviation around the mean for these variables suggest a balanced distribution suitable for the statistical analysis to be pursued in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes basic descriptive statistics of the independent variables selected for analysis. Foliar moisture content, canopy base height, and wind speed are three fire environment variables that theoretically are major factors controlling the onset of crowning and have already been used in modeling this phenomenon (Van Wagner 1977a, Xanthopoulos 1990, Alexander 1998Cruz et al 2002). The range and deviation around the mean for these variables suggest a balanced distribution suitable for the statistical analysis to be pursued in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…From a fire management perspective, knowledge of the onset of crowning is of critical importance from a safety and tactical standpoint, yet few research attempts have been directed at explaining and/or developing models to predict this feature of wildland fire behaviour (Van Wagner 1977a, Xanthopoulos 1990, Alexander 1998, Cruz 1999. This lack of attention probably can be explained by (1) the unknowns in fundamental combustion and heat transfer theory in wildland fuels, (2) the difficulty in replicating such phenomena in a laboratory setting, and (3) the difficulty of instrumenting outdoor high-intensity experimental fires in order to quantitatively describe the influence of relevant variables, important physical processes, and their outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of ignition and subsequent flame spread of forest fuels has largely been performed using dried and dead fuels and only a few works were found that examined live fuels [12,13,14,15,16]. Dimitrakopoulos and Papaioannou [12], Jervis et al [13], McAllister et al [14], all studied ignition due to radiative heating.…”
Section: Introductionmentioning
confidence: 99%
“…Dimitrakopoulos and Papaioannou [12], Jervis et al [13], McAllister et al [14], all studied ignition due to radiative heating. Xanthopoulos and Wakimoto [16] and Fletcher and coworkers ( [15, 17, and 18]) were the only studies found that convectively heated live fuels to ignition. However, the study in [12] was primarily focused on developing an empirical correlation for the ignition time rather than investigating the physical processes involved in ignition.…”
Section: Introductionmentioning
confidence: 99%